PENGELOLAAN BADAN USAHA MILIK DESA (BUMDES) TERHADAP PENINGKATAN PENDAPATAN ASLI DESA ????PADES???? DESA BATETANGNGA KECAMATAN BINUANG KABUPATEN POLEWALI MANDAR PROVINSI SULAWESI BARAT - Rahmawati Sururama; Andy Ariskha Masdar (PRODI ADMINISTRASI PEMERINTAHAN DAERAH FAKULTAS MANAJEMEN PEMERINTAHAN IPDN, 2020)
Village-Owned Enterprises, hereinafter referred to as BUMDes or BUM Desa, are business entities whose entire or most of their capital is owned by the Village through direct participation from village assets that are separated for the management of assets, services, and other businesses for the welfare of the village community. BUMDes Batetangnga is a BUMDes that was established right in the Village of Batetangnga, one of the villages located in the District of Binuang, Polewali Mandar Regency, West Sulawesi Province.This research aims to analyze the management of Village-Owned Enterprises (BUMDes) Towards Increased Village Original Income (PADes) Batetangnga Village, Binuang District, Polewali Mandar Regency, West Sulawesi Province. This research uses descriptive method with inductive approach. Data collection techniques are done through observation, interviews and documentation. The data analysis technique usedis ????ishbone analysis. Based on the results of research conducted, BUMDes Batetangnga is a BUMDes which is considered quite good, but there are still some shortcomings. The most prominent problem is the decline in BUMDes revenue in 2018 due to several factors. Then the other problem is related to the problem of human resources management of BUMDes Batetangnga which is considered not to have maximum knowledge and still needs to be developed and improved